1997
DOI: 10.1103/physreve.56.5450
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the rotational degrees of freedom in a supercooled liquid of diatomic molecules

Abstract: Using molecular dynamics computer simulations, we investigate the dynamics of the rotational degrees of freedom in a supercooled system composed of rigid, diatomic molecules. The interaction between the molecules is given by the sum of interaction-site potentials of the Lennard-Jones type. In agreement with mode-coupling theory (MCT), we find that the relaxation times of the orientational time correlation functions C (s)2 (t) and C 1 (t) show at low temperatures a power-law with the same critical temperature T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
213
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(265 citation statements)
references
References 40 publications
(73 reference statements)
46
213
2
Order By: Relevance
“…These results were also found for a system of nonpolar molecules. 9,10 When fitting D r to a power law, a critical temperature of 58 K is obtained, which is lower than those associated with translational and reorientational relaxation times, and also with translational diffusion coefficients. Then, rotational dynamics about a direction perpendicular to the molecular axis is less hindered than translational dynamics upon cooling, and it is still active when translational dynamics is already frozen.…”
Section: B Reorientation and Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were also found for a system of nonpolar molecules. 9,10 When fitting D r to a power law, a critical temperature of 58 K is obtained, which is lower than those associated with translational and reorientational relaxation times, and also with translational diffusion coefficients. Then, rotational dynamics about a direction perpendicular to the molecular axis is less hindered than translational dynamics upon cooling, and it is still active when translational dynamics is already frozen.…”
Section: B Reorientation and Rotationmentioning
confidence: 99%
“…Rotational dynamics and its connection with translation has been analyzed in simulations of several molecular glass formers as ortho-terphenyl 5 and water, 6,7 where a decoupling was encountered. 8 For a model system of rigid dumbbells it has been found that jumps are important at temperatures close to the critical one, 9 and that angular jumps are more relevant than translational ones in the deeply supercooled liquid. 10 The analysis of the translational-rotational coupling in that nonpolar system has raised some questions on the adequacy of the diffusive model to describe rotational dynamics in the supercooled state.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon is expected to be present in the studied system at small ζ, preventing the possibility of an accurate determination of the asymptotic laws close to the MCT critical temperature T B c . In addition, we recall that ideal MCT neglects activated processes which are known to be present in reality around and below T B c [10]. Only when hopping phenomena can be neglected, an MCT study can be feasible very close to T To provide a lower bound to T B c at small ζ, we also fit the data in terms of the well-known phenomeno-…”
mentioning
confidence: 99%
“…It has now become apparent that the ideal modecoupling theory (MCT) for structural relaxation [2,8] contains the essential ingredients for the description of the molecular dynamics in supercooled states, down to a cross-over temperature T c , where "hopping" processes become dominant [9,10]. Although the MCT was originally developed for simple (atomic) liquids, it appears to be able to rationalize in a coherent way experimental [3,11,12] and numerical simulation results [6,13,14] also for molecular liquids, i.e. for molecules with anisotropic interaction potentials.…”
mentioning
confidence: 99%